Leitura e produção do gênero publicitário em sala de aula - Mendes, Sara Elisa Machado (2014)
This work is part of the research line "Text, speech, and education: reading processes and written text production and spoken. It is entitled "Reading and Writing of the advertising genre in the classroom." The objective of this study is to see how the genre approach presented in the curriculum of the State of São Paulo has been implemented in classrooms by the teachers, and its effectiveness. Thus, the study focused on the analysis of reading and writing activities of advertisement genres in Portuguese classes in the eighth grade of elementary school in the State System of the São Paulo State Education. In developing this work, we observed the dynamics of the genre approach in the classroom checking the adaptations made by teachers to achieve the objectives proposed by the Curriculum and analyze the productions of the students in response to this proposal. The work is based on social-interactionists theories as proposed by Schneuwly, Dolz (2011 ), Bronckart (1997 ); the approach to teaching by genres as Marcuschi; Bazerman (1994); in Discourse Analysis, with the contribution of Bakhtin (2010 ) and his dialogical conception of language; in reading strategies proposed by Solé (1998 ). Knowing to teach different multiliteracies present in the various existing genres is an essential task for the teacher. Reading and text production falls within that framework in a broader conception of what are the relationships that gender, embodied in the text, proposes a challenge to the teacher in the classroom by their way of interweaving, overlapping and weave the world outside school and the world of the classroom. The activities, in this view, are not limited to the time during the lesson; therefore the analyzes of this study include the proposal of the official materials and teachers as well as the resulting production of students. The results indicate that more active participation of the teacher in the appropriation of activity is needed, and proposing more appropriate training may be in action as noted in this research.